Financial literacy toolkit for Islamic investment - Mohd Noor, Nor Halida Haziaton; Wan Yusof, Wan Yusrol Rizal; Abu Bakar, Noridah; Mohd Roslen, Siti Nurhidayah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
In today's fast-paced society, financial literacy often lacks engaging and accessible resources, despite a growing need for practical information. The Muslim community has a substantial knowledge and application gap as a result of the intricate way Islamic investment concepts are presented. The ‘Financial Literacy Toolkit for Islamic Investment’ (FINALTII) is an interactive educational toolkit designed to bridge this gap by educating users about Islamic investment. Created using online resources, it features captivating infographics and comic- style visuals that transform complex information into relatable, easy-to-understand content while focusing on Shariah-compliant investments such as property, stocks, commodities, and mutual funds. This product highlights core principles of Islamic finance while creatively illustrating investment concepts through everyday experiences. The potential impact of this innovation extends beyond individual comprehension. By enhancing Islamic financial literacy, the toolkit aims to empower communities, fostering economic growth and stability. As an educational tool for individuals and Islamic institutions at both national and international levels, it supports the development of informed investors, ultimately contributing to a more resilient socioeconomic landscape. Upon its market introduction, we anticipate it will significantly raise public awareness and understanding of Islamic investment, paving the way for increased socio-economic development within the community.